How Semiphysiological Population Pharmacokinetic Modeling Incorporating Active Hepatic Uptake Supports Phase II Dose Selection of RO7049389, A Novel Anti–Hepatitis B Virus Drug. Issue 4 (10th March 2021) - Cosson, Valérie; Feng, Sheng; Jaminion, Felix; Lemenuel‐Diot, Annabelle; Parrott, Neil; Paehler, Axel; Bo, Qingyan; Jin, Yuyan
Abstract : The pharmacokinetics (PK) of RO7049389, a new hepatitis B virus (HBV) core protein allosteric modulator of class I, and of its active metabolite M5 were studied in fasted and fed conditions after single and multiple once‐a‐day and twice‐a‐day doses in healthy subjects and patients with HBV. The nonlinearity of the pharmacokinetics, the large variability, the small sample size per dose arms, the higher plasma exposure in Asians, and the heterogeneity in patient baseline characteristics seen in phase I studies made the ethnic sensitivity assessment and the selection of the recommended phase II dose difficult. A population PK model, simultaneously modeling RO7049389 and M5, was developed to characterize the complex PK, quantify ethnicity (i.e., Asian vs. non‐Asian) and gender effects on the PK of RO7049389 and M5, and infer the quantity of RO7049389 in liver relative to plasma. Exposures in the liver are of particular importance for dose selection since the liver is the site of action of the compound. The model described and reproduced the population PK profiles as well as the between‐subject variability of RO7049389 and its metabolite. It could show that the PK is similar between healthy subjects and in HBV patients, once the ethnicity and gender effects are accounted for. The model predicts that, despite a large difference in the plasma exposure of RO7049389 between Asians and non‐Asians, the exposure in the liver is comparable, allowing the use of the same dose to treat Asian and non‐Asian patients. This model provides a valuable basis to develop this new anti‐HBV drug and to define optimal dosing.